The Americans With Disabilities Act Implications for Family Counselors: Counseling Students in Higher Education. (January 2021) - Phillippe, Larry K.; Noble, Nicole; Hendricks, Bret; Brendle, Janna; Lock, Robin H.
Family counselors at times work with families in which a family member with a disability is transitioning into higher education settings. Frequently, these counselors are unaware of the federally protected rights of all students and they may not know how to access this information. This article explains the differences between laws for students with disabilities in K–12 school settings and the components of the Americans with Disabilities Act (ADA) and its subsequent ADA 2008 Amendments to inform family counselors on how to support clients and their families in the transition to higher education. In this article, the authors discuss the ADA and the ADA 2008 Amendments, which dramatically impacted the college experience of all students with disabilities. With record numbers of students with disabilities now attending college, counselors, as they advocate for families, should be aware of federal guidelines that require physical access to educational facilities, the use of universal design, electronic accessibility, and the provision of academic accommodations and modifications in college classrooms. Through family counselors' awareness of these significant changes in the higher education experience, they can more fully assist families with students with disabilities who are transitioning from high school to higher education. This article describes each of these four facets of the ADA 2008 Amendments as well as the impact each major facet of the amendment has on the higher education landscape for students with disabilities.